Pengaruh Literasi Pajak, Moral Pajak Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Digitalisasi Pajak Sebagai Moderasi - Elfriska Elfriska; R. Septian Armel; Siti Samsiah (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2025)
. This study aims to examine the effect of tax literacy, tax morale and tax socialization on individual taxpayer compliance with tax digitalization as a moderating variable. In this study, the data used is primary data with a data collection method using a questionnaire. The population in this study were Individual Taxpayers at KPP Pratama Pekanbaru Senapelan. Sampling using the simple random sampling method. There were 142 respondents who were the samples in the study. This study is a quantitative study with data obtained processed using IBM Statistics SPSS 25. The results of the study indicate that taxpayer awareness, tax sanctions and risk preferences of tax literacy, tax morale and tax socialization partially influence individual taxpayer compliance at KPP Pratama Pekanbaru Senapelan. Tax digitalization can moderate the relationship between tax literacy, tax morale and tax socialization on individual taxpayer compliance at KPP Pratama Pekanbaru Senapelan. Keywords: Tax Literacy, Tax Morale, Tax Socialization, Tax Digitalization Taxpayer Compliance